Effect of serotonin 7 receptors and transcript variants on RIN-5F pancreatic beta cell line - Yayla, Muhammed; Toktay, Erdem; Ozdemir Sarikaya, Bengul; Ermis, Ugur; Akgun, Sakir; Cinar, Irfan (Elsevier BV, 2025)
The physiological effects of 5-HT7 receptors expressed in pancreatic beta cells have not yet been elucidated. We first aimed to investigate the effect of 5-HT7 receptor agonist (AS19) and antagonist (SB269970) application on insulin secretion in RIN-5F pancreatic beta cells. Subsequently, we aimed to investigate the effects of agonist and antagonist applications on cell damage induced by STZ.Cell damage was caused by giving 5 mM STZ solution to the cells for 12 h. The protective effects of 5-HT7 receptor agonist and antagonist on this subsequent damage were investigated. IGF-1, TNF-α, TGF-B1, NF-KB, Bax, Caspase 3, Caspase 9, 5-HT7, 5HT7x2, 5HT7x3 mRNA expression levels were compared between groups.While agonist application stimulates insulin secretion, the effect of the antagonist varies.SB269970 reduced oxidative stress and downregulated TNF-a, TGF-B1 and NF-KB expression and also prevented apoptosis by decreasing Bax, caspase 3 and 9 levels against STZ-induced beta cell damage.The effect of 5-HT7 receptors on insulin secretion and their effects against STZ damage will be guiding for more detailed studies in the treatment of diabetes and related diseases in the future.
Keywords: Sulfonamides; Apoptosis; Streptozocin; Rats; Cell Line; Serotonin Receptor Agonists; Oxidative Stress; Insulin-Secreting Cells; Receptors, Serotonin; Insulin Secretion; Animals; Insulin; Serotonin Antagonists; RNA, Messenger